OCCURRENCE OF THE PUERULUS OF THE SPINY LOBSTER PANULIRUS POLYPHAGUS (HERBST) IN ZUARI ESTUARY IN GOA - Thomas, P A (Indian Journal of Fisheries, 2011)
The occurrence of the puerulus larvae of the marine spiny lobster, Panuliruspolyphagus (Herbst) is reported from the estuarine waters of Goa.